2020
DOI: 10.34257/gjmrbvol20is2pg19
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant, Anti-Inflammatory And Anti-Microbial Activity of Carica Papaya Seeds

Abstract: Papaya seeds are reported to have higher therapeutic potential in comparison to the fruits in which they reside. Thus, the present in-vitro study aimed to evaluate and compare the anti-oxidant, anti-inflammatory and anti-microbial effect of seed extracts on Carica papaya L. (Caricaceae). The bioactive form the seeds were sequentially fractionated with hexane, chloroform, diethyl ether, and methanol in the increasing order of polarity. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We found that the concentration-dependent activity of AgNPs was 56% for synthesised AgNPs and 38% for commercially available CPPE [ 39 ]. According to a recent study, the antioxidant activity of methanolic extract of papaya leaf was assessed by measuring its ability to neutralise free radicals (DPPH) [ 40 ]. DPPH free radical scavenging capacity was found to be best in hexane extract and lowest in aqueous extract in another investigation using papaya seed extracts and the results showed [ 41 ].…”
Section: Bioactivities Of Papaya Leaf Extractmentioning
confidence: 99%
“…We found that the concentration-dependent activity of AgNPs was 56% for synthesised AgNPs and 38% for commercially available CPPE [ 39 ]. According to a recent study, the antioxidant activity of methanolic extract of papaya leaf was assessed by measuring its ability to neutralise free radicals (DPPH) [ 40 ]. DPPH free radical scavenging capacity was found to be best in hexane extract and lowest in aqueous extract in another investigation using papaya seed extracts and the results showed [ 41 ].…”
Section: Bioactivities Of Papaya Leaf Extractmentioning
confidence: 99%
“…In recent years, the flavonoids and non-flavonoids phenolics, in all their types and structures (Figure 1), obtained from tropical fruits and their coproducts have aroused the interest of different fields, such as biomedical science and food technology. This interest in these bioactive compounds is due to their numerous biological effects including antioxidant [12,13], hypo-cholesterolemic [14,15], anticancer [16,17], immunomodulatory [18], anti-inflammatory [19,20], anti-diabetic [21,22] and anti-hypertensive [23,24], among others. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Amandeep Singh et al, evaluated in-vitro antiurolithiatic activity of Carica papaya roots belong to family Caricaceae revealed aqueous and alcoholic extracts of C. Papaya roots on ethylene glycol (EG) induced urolithiatic rats. Root extract of Carica papaya shows decrease in the calcium oxalate crystals with the dilution of 10mg/ml,40mg/ml, 80mg/ml 20 .…”
Section: Carica Papayamentioning
confidence: 95%